Partisipasi Generasi Muda Dalam Pengembangan Ekowisata Subak Sembung di Desa Peguyangan, Denpasar Bali - Ni Nyoman Astriani Giri; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Subak Sembung Ecotourismhas width of 155 hectares, administratively a part of Peguyangan village, North Denpasar subdistrict. The existence of this Subak Ecotourism is a green line left in Denpasar city. The purposes of this research are to determine the development of Subak Sembung as ecotourism destination in Peguyangan village, Denpasar, Bali and to determine about the role of youth generation ofSubak Sembung Ecotourism development in Peguyangan village, Denpasar, Bali. The data used inthis research is qualitative data with the data sources in the formof primary data and secondary data. Those data collected using method of observation, in-depth interview, and literature study. The determining of informants done by purposive technique. The result of this research show that the youth generation of Banjar Pulugambang actively participate in tourism activities such as involved in events that held by Subak Sembung Ecotourism manager. Their roles are as the guest greeters, classified in a cimittee as food and drinks keepers, handicraft accessories keepers, and also involved as a local guide, help in decorating, keep the environment clean, and do events such as fishing, guiding inmaking canang, outbound, teaching the tourists to painting and also teaching the tourist to dance. The theory of Tosun explains that the participation of youth generation from Banjar Pulugambang has done spontanly. Keywords : Role of youth generation,Ecotourismdevelopment, Subak.